The Comparison of Lithuanian Written and Electronic Discourse (The Most Frequently Used Words, Word Forms and Keywords) - Ryklienė, Asta (Kalbotyra, 2001)
The article presents the comparison of two different varieties of Modern Lithuanian. i.e. written (WL) and electronic (used for communication on the Internet, ED) built on analysis of the most frequently used words, word forms and keywords.The comparison of lists of the fifty and one hundred most frequently used words and fifty most frequently used word forms, as well as the list of keywords, revealed some differences between WL and ED. There are more verbs, adverbs and particles among the most frequently used words and word forms in ED than in WL, whereas WL has more nouns. There are more subordinating conjunctions in ED and co-ordinating conjunctions in WL. First person pronouns are used more frequently than third person pronouns in ED, while third person pronouns dominate in WL. An important difference between ED and WL is related to the usage of informal vocabulary (non-standard and obscene words) in ED, but not in WL. Some linguistic features of language economy and redundancy and the dialogic form of speech were identified in ED.It is concluded that ED significantly differs from WL and has some features which show its resemblance to spontaneous spoken language.